A divergent synthesis of secologanin derived natural products - English, Brandon Joel, author; Williams, Robert M., advisor; Ferreira, Eric M., committee member; Eckstein, Torsten, committee member; Elliott, C. Michael, committee member; Finke, Richard G., committee member (Colorado State University. Libraries, 2010)
This dissertation documents the racemic total synthesis of the natural products oleocanthal, geissoschizol, corynantheidol, dihydrocorynantheol, protoemetinol, and 3-epi-protoemetinol from a single synthetic intermediate. Also described are efforts to produce an optically pure supply of the common synthetic intermediate of the above described natural products. The work described herein represents the first steps toward the development of a general strategy capable of synthesizing several structurally diverse members of the family of compounds derived from secologanin.
Department Head: Ellen R. Fisher.
Keywords: Secologanin; corynantheidol; oleocanthal; geissoschizol; dihydrocorynantheol; protoemetinol; Biosynthesis; Organic compounds -- Synthesis; Enantiomers -- Biotechnology